The feasibility of using 18F-FDG-PET/CT in patients with mucinous breast carcinoma. Issue 11 (November 2018) - Fujioka, Tomoyuki; Kubota, Kazunori; Kikuchi, Yuka; Tsuchiya, Junichi; Tateishi, Ukihide; Kasaharak, Mai; Oda, Goshi; Ishiba, Toshiyuki; Nakagawa, Tsuyoshi
Abstract : Purpose: This study investigated the correlation between fluorine-18-fluorodeoxyglucose ( 18 F-FDG)-PET/computed tomography (CT) and clinicopathological factors in patients with mucinous breast carcinoma and assessed the feasibility of using 18 F-FDG-PET/CT in evaluating tumors. Patients and methods: We retrospectively examined 42 consecutive patients with pathologically proven mucinous breast carcinoma who preoperatively underwent 18 F-FDG-PET/CT. In addition, we compared 18 F-FDG uptake with clinicopathological characteristics. Results: 18 F-FDG uptake was observed in 39 (92.9%) lesions. The maximum standardized uptake value (SUVmax ) (mean±SD) of all mucinous carcinoma, pure type, and mixed type was 2.3±1.3 (range: 1.0–5.1), 1.9±0.9 (range: 1.0–3.5), and 3.2±1.3 (range: 1.4–5.1), respectively. The mixed type had a significantly higher 18 F-FDG uptake than the pure type ( P =0.006). In addition, the sensitivity, specificity, accuracy, and area under the curve for distinguishing the pure type from the mixed type were 61.5, 89.7, 81.0, and 0.76, respectively (cutoff value: SUVmax >3.0). Furthermore, SUVmax correlated significantly with the high nuclear grade ( P =0.010) and the presence of axillary lymph node metastasis ( P =0.017). Conclusion: 18 F-FDG uptake efficiently distinguishes the pure type from the mixed type and may play a potential role in predicting the aggressiveness of mucinous breast carcinoma.